Fenomena Cyber Religion dalam Transformasi Praktik Keberagamaan di Era Digital (Studi Kasus Komunitas Shift) - Huri, Vivi Silvia; Andriana, Anggia Rita; Sarbini, Ahmad; Setiawan, Asep Iwan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This research is motivated by the increasing interest of modern young people in religious practices through digital spaces, particularly in the context of changing patterns of religious interaction from physical spaces to social media-based platforms. The purpose of this research is to analyze how the concept of cyber religion applied in the Shift Community triggers a transformation of religious practices from traditional hierarchical models to digital religiosity that is aesthetic, participatory, and adaptive to media culture. This research uses qualitative methods with descriptive analysis techniques through case studies, observations of digital content, and a literature review on the mediatization of religion and the Uses and Gratifications theory. The results of the study indicate that da'wah has shifted from a one-way lecture model to an emotional visual narrative that is creatively packaged and easily accepted by the younger generation, accompanied by active participation of digital congregations through collaborative content reproduction and distribution. The findings also indicate a shift in religious authority from a central figure to the distribution of meaning through community interactions, as well as the formation of religious identities based on personal branding and spiritual practices influenced by social media algorithms. The implications of the study emphasize that digitalization can expand the reach of da'wah and create new spiritual experiences, but strengthening digital literacy and da'wah ethics is still necessary to avoid the commercialization of religion and the reduction of the meaning of spirituality.